Principles of the pedagogical system of master of the realistic painting and graphic arts. artist-painter of battlepieces - N.S. Samokisha (Pedagogy of Higher and Secondary Education, 2009)
"Principles of the pedagogical system of master of the realistic painting and graphic arts. artist-painter of battlepieces - N.S. Samokisha" is examined question about the features of artistic-pedagogical activity of the known Ukrainian artist of large and scalene talent Mickolaja Se- menovicha Samokisha, individually his innovative elucidative measures and methods on teaching of artists- painters of battlepieces.
Keywords: artistic-pedagogical activity; pedagogical principles; pedagogical system; innovative methods; battle genre; painting; graphic arts; animalistic game